Perencanaan Strategis Sistem Informasi Menggunakan Metode Ward & Peppard (Studi Kasus : Ekspedisi Rahayu Mandiri) - Bagas Rizky Alviansyah; Chris Rudianto (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Ekspedisi Rahayu Mandiri is a freight forwarding service provider engaged in the field of expedition services. The activity of recording all expedition data is still manual and has not been implemented in IS/IT. This becomes an obstacle in the management of expedition data. The existence of IS/IT technology is a support for a company in facilitating work and maximizing company performance. The importance of Information Systems in the management and development of business performance is very helpful for the effectiveness and efficiency of the company. In implementing IS/IT, it is necessary to have a good and well-targeted Information System Strategy Planning, in order to produce maximum IS/IT implementation. This study uses the Ward and Peppard methodology with several analyzes namely SWOT, Porter's Five Forces, and McFarlan Strategic Grid. The results of the research are internal and external environmental factors of IS/IT in the scope of the expedition. These results can recommend an information system strategy by mapping strategic planning and its implementation in the future.